The Influence of Participative Leadership Style and Supervision on Performance of PT Sampoerna Agro TBK Sukamara Central Kalimantan Employees - Andri Asoka Sidantara Rosadi; Muhammad Faisal Syaban (International Journal of Integrative Sciences, 2023)
This research was conducted on employees at PT SampoernaAgro Sukamara, Central Kalimantan.This research aims to determine how much influence participative and supervisory leadership styles have on employee performance simultaneously or partially. This research uses descriptive methods and associative methods. The unit of analysis for this research is employees at PT SampoernaAgro Tbk Sukamara, Central Kalimantan. This research used 60 respondents as samples. Saturated sampling is used in sampling.   Apart from multiple linear regression analysis, this research also uses validity and reliability tests on    research instruments. Referring to the research results, it indicates a partial or simultaneous influence on the independent variables (participative leadership style and supervision) on   the dependent variable (employee performance).   The implication of this research is that increasing   participatory and supervisory leadership styles will create maximum employee performance